2019
DOI: 10.1039/c9ra06272f
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the organic fouling mechanism of an in situ Ca2+ modified thin film composite forward osmosis membrane

Abstract: In this study, the effect of organic substances on the fouling behavior of a thin film composite (TFC) membrane with in situ Ca2+ addition (TFC-Ca membrane) was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Some studies discussed membrane fouling properties as a result of feed high concentration (BOD and other biological contaminants) [86,87]. Here, TFCs have been generally used with one active layer to control membrane fouling [88]. Draw solution facing the open channels in membranes were exposed to highly concentrated draw solute, resulted in high reverse solute flux.…”
Section: Membrane Properties and Fouling Behaviormentioning
confidence: 99%
“…Some studies discussed membrane fouling properties as a result of feed high concentration (BOD and other biological contaminants) [86,87]. Here, TFCs have been generally used with one active layer to control membrane fouling [88]. Draw solution facing the open channels in membranes were exposed to highly concentrated draw solute, resulted in high reverse solute flux.…”
Section: Membrane Properties and Fouling Behaviormentioning
confidence: 99%
“…14,15 Moreover, electrolytes could also interact with the modied membrane surface. 16,17 Luo et al 18 found that Ca 2+ can bind the carboxyl groups between whey protein and the negatively charged polyamide membrane surface to aggravate membrane fouling. Zwitterionic material which has two opposing electrical groups can adsorb abundant electrolytes especially bivalent cations as well, 19 which may inuence the interaction with foulants.…”
Section: Introductionmentioning
confidence: 99%
“…Zazouli et al [15] found that individual alginate fouling was more detrimental than individual humic acid fouling. Hao et al [21] evaluated the effect of organic substances on the fouling behavior of a thin film composite (TFC) membrane with in situ Ca 2+ addition.…”
Section: Introductionmentioning
confidence: 99%